On the Dynamics of the Ionosphere - MAEDA, Ken-ichi (Proceedings of the Japan Academy, Series B, 1991)
The conductivity elements, σ1(Pedersen) and σ2 (Hall) are derived, taking into account the coupling through collision between neutrals, ions and electrons. In the course of the above work the so-called generalized Ohm's law is obtained. By investigation of dynamo current it is found that the elements of conductivity tensor have their own phase. The velocity components have also their own phase and it is found that unexpectedly low altitude of the upper limit of the active dynamo layer revealed by rocket experiments, can be well understood when we notice the phase of the velocity components.